Framing sustainable energy : a comparative analysis of Malay and English newspaper in Malaysia - Mohamed, Shafizan; yusoh, Helmi; Wan Mohd Ghazali, Wan Norshira (AESS Publications, 2020)
This study aims to examine how mainstream newspapers in Malaysia frame sustainable energy. Framing is the perspective or the angle taken by newspapers when writing about a news story. How newspapers frame sustainable energy is a very important indication of how the issue is perceived by the public mostly because the media is where most people get their news and information regarding environmental and sustainability issues. A deductive, quantitative methodological approach was used to identify dominant frames and news sources in articles published in four Malaysian newspapers: News Straits Times, The Star, Berita Harian and Harian Metro between January 2018 and September 2019. Media framing theory was employed as the framework for analysis. The findings suggest that while the English and Malay newspapers shared some similarities in the way they covered sustainable energy, it is the English newspapers that are more proactive in driving the readers to be more engaged with the issue. In addition, this study extends our understanding of the contextual conditions that enable and limit journalists when reporting environmental and sustainability issues.